2003
DOI: 10.1111/j.0014-3820.2003.tb01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Transfer by Hummingbirds and Bumblebees, and the Divergence of Pollination Modes in Penstemon

Abstract: We compared pollen removal and deposition by hummingbirds and bumblebees visiting bird-syndrome Penstemon barbatus and bee-syndrome P. strictus flowers. One model for evolutionary shifts from bee pollination to bird pollination has assumed that, mostly due to grooming, pollen on bee bodies quickly becomes unavailable for transfer to stigmas, whereas pollen on hummingbirds has greater carryover. Comparing bumblebees and hummingbirds seeking nectar in P. strictus, we confirmed that bees had a steeper pollen carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
183
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(190 citation statements)
references
References 47 publications
6
183
1
Order By: Relevance
“…This could be the main reason for the decline in the pollen transfer efficiency of halictid bees in the manipulated treatment. In some other studies, researchers have also indicated that the pollen available for pollination would rapidly decline and that pollination efficiency would decrease if plants were visited by pollen-collecting pollinators (Castellanos et al 2003; Young et al 2007). Notably, under such circumstances, sequential stamen maturation (staggered pollen presentation) could be a mechanism to increase the pollen transfer efficiency of pollinators in order to alleviate the effect of diminishing returns on pollen transfer.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the main reason for the decline in the pollen transfer efficiency of halictid bees in the manipulated treatment. In some other studies, researchers have also indicated that the pollen available for pollination would rapidly decline and that pollination efficiency would decrease if plants were visited by pollen-collecting pollinators (Castellanos et al 2003; Young et al 2007). Notably, under such circumstances, sequential stamen maturation (staggered pollen presentation) could be a mechanism to increase the pollen transfer efficiency of pollinators in order to alleviate the effect of diminishing returns on pollen transfer.…”
Section: Discussionmentioning
confidence: 99%
“…One flower type, the generalist flower, is blue and is efficiently pollinated by bees and birds alike. The blue Rocky Mountain penstemon, Penstemon strictus, provides a good example (Castellanos et al 2003). The other flower type, or bird flower, is yellow and is efficiently pollinated by birds, but not by bees—the red beardlip penstemon P.…”
Section: Niche Partition and The Evolution Of Red Flowersmentioning
confidence: 99%
“…The other flower type, or bird flower, is yellow and is efficiently pollinated by birds, but not by bees—the red beardlip penstemon P. barbatus provides an example of this type (Castellanos et al 2003). If bee visits were costly for the ancestral bird flowers, they would experience a selective pressure to become red.…”
Section: Niche Partition and The Evolution Of Red Flowersmentioning
confidence: 99%
“…This is, especially, evident in F. olgae , a species that produces copious, but rather dilute, sucrose-rich nectar (Castellanos et al, 2003). …”
Section: Discussionmentioning
confidence: 99%